Exploring absolute and relative measures of exposure to food environments in relation to dietary patterns among European adults. Issue 6 (7th December 2018) - Pinho, MGM; Mackenbach, JD; Oppert, J-M; Charreire, H; Bárdos, H; Rutter, H; Compernolle, S; Beulens, JWJ; Brug, J; Lakerveld, J
Abstract: Objective: To explore the associations of absolute and relative measures of exposure to food retailers with dietary patterns, using simpler and more complex measures. Design: Cross-sectional survey. Setting: Urban regions in Belgium, France, Hungary, the Netherlands and the UK. Participants: European adults ( n 4942). Supermarkets and local food shops were classified as 'food retailers providing healthier options'; fast-food/takeaway restaurants, cafés/bars and convenience/liquor stores as 'food retailers providing less healthy options'. Simpler exposure measures used were density of healthy and density of less healthy food retailers. More complex exposure measures used were: spatial access (combination of density and proximity) to healthy and less healthy food retailers; density of healthier food retailers relative to all food retailers; and a ratio of spatial access scores to healthier and less healthy food retailers. Outcome measures were a healthy or less healthy dietary pattern derived from a principal component analysis (based on consumption of fruits, vegetables, fish, fast foods, sweets and sweetened beverages). Results: Only the highest density of less healthy food retailers was significantly associated with the less healthy dietary pattern ( β = −129·6; 95 % CI −224·3, −34·8). None of the other absolute density measures nor any of the relative measures of exposures were associated with dietary patterns. Conclusions: More complex measures of exposure to food retailers did not produce stronger associations with dietary patterns. We had some indication that absolute and relative measures of exposure assess different aspects of the food environment. However, given the lack of significant findings, this needs to be further explored.